2014
DOI: 10.18517/ijaseit.4.5.427
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Agricultural Credit on Rice Productivity

Abstract: This study investigates the impact of credit access on agriculture productivity in Indonesia using provincial level data. Credit access is deemed to have positive impact on productivity since it provides farmers with resources needed to start the production process. Thus, greater access to credit can induce agriculture production and support government program for food security which is very important for Indonesia, the fourth-largest country in the world in term of population. Indonesian government has given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 0 publications
3
11
0
Order By: Relevance
“…This suggests that agricultural credit access would decrease rice production inefficiency. This result is consistent with the results from Sjah et al (2003) and Wicaksono (2014). Ethnicity is significant at 10% that means Fulani are more inefficient in rice cultivation than other ethnics in Anambe area.…”
Section: Descriptive Statisticssupporting
confidence: 92%
See 1 more Smart Citation
“…This suggests that agricultural credit access would decrease rice production inefficiency. This result is consistent with the results from Sjah et al (2003) and Wicaksono (2014). Ethnicity is significant at 10% that means Fulani are more inefficient in rice cultivation than other ethnics in Anambe area.…”
Section: Descriptive Statisticssupporting
confidence: 92%
“…The results indicated that credit constraints hinder farmers' production performance. Sjah et al (2003) and Wicaksono (2014) also got the similar conclusions and pointed that agricultural credit has stronger influences on the intensified farming. Enyim et al (2013), applied the unit-root cointegration to investigate the relationship between banking sector credits and agricultural activities in Nigeria.…”
Section: Introductionmentioning
confidence: 64%
“…Credit receipt allows farmers to purchase improved seeds, fertilizer, and pesticides and use more efficient production methods that ultimately enhance the productivity of the farmers. Prior studies found that a 10% increase in agricultural credit is associated with 1.2 ton per hectare increase in productivity [47], and paddy production can be increased 8.5% by increasing credit by 10% [48]. Not surprisingly, we found farmers that used more mechanization, and more advanced irrigation methods had higher yields.…”
Section: Discussionsupporting
confidence: 48%
“…Empirical assessments of the effect of access to credit on productivity in past studies have shown mixed results. Some of these studies have shown that access to credit has a positive and statistically significant impact on productivity (Ayaz and Hussain, 2011; Bashir et al , 2010; Chisasa and Makina, 2013; Dong et al , 2010; Feder et al 1990; Gomina et al , 2015; Iqbal et al , 2003; Wicaksono, 2014). In other words, with access to credit, farmers are able to shift their production frontier outwards.…”
Section: Introductionmentioning
confidence: 99%